Two new species of Platypona DeLong (Hemiptera: Cicadellidae: Iassinae: Gyponini) from Peru and key to the species of the genus - Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda; Takiya, Daniela Maeda; Mejdalani, Gabriel (Zootaxa, 2014)
Two new species of the previously monotypic genus Platypona DeLong, 1982 from Peru are described and illustrated: P. furcata sp. nov. (Cusco Department) and P. inca sp. nov. (Pasco Department). These two species can be distinguished from each other, as well as from the type-species, P. sinverda DeLong, 1982, mainly by features of the style and aedeagus. A key to the three known species of Platypona is provided.